THE EFFECT OF RIDDLE GAMES TO IMPROVE VOCABULARY OF EIGHT GRADERS AT SMP SATAP NEGERI NIAN - Neno, Priskilia Febriani Sara; Semiun, Thresia Trivict; Bouk, Edmundus (JELT (Jambi-English Language Teaching), 2025)
This research aimed to determine the effect of riddle games on improving the vocabulary achievement of the eight graders at SMP Satap Negeri Nian. The research subject was class VIII A, which consists of 20 students. This research design was pre-experimental with a pre-test and post-test design. The students did a pre-test, received treatment, and did a post-test. The research results indicated increased students' vocabulary achievement—the average post-test score was 77, more than the pre-test 45. For a level of significance (α) of 5% and df = 19, the table value was 1.729, and the t-test value was 1.68. It showed that the t-test value was more significant than the t-table (1.68 ≥ 1.729). Thus, teaching vocabulary using riddle games significantly influenced vocabulary. The students' vocabulary was classified as fair, good and excellent.